The asymmetric approach in Russian security strategy: implications for the Nordic countries - Pynnöniemi, Katri (Terrorism and political violence, 2019)
Two observations stand out from the Russian strategic outlook. First, it corresponds with the real politik vision of world politics where the states engage in (zero-sum) competition for power and resources. Second, the new world order emerges because of a conflict between different models of development and value systems. These two observations highlight a certain “family resemblance” between the current Russian assessment of the current security environment and the situation during the Cold War. Furthermore, Russian national security strategy is oriented toward achieving strategic stability with the other great powers. The maintenance of strategic parity (nuclear and conventional deterrence) is a means to this end. However, given Russia’s relative weakness in comparison to its major geopolitical competitors, this has led to the renewal of the Cold War-era concept of asymmetric approach. Although this concept is most often used in the context of nuclear deterrence and the debate on “strategic stability,” it is not about military security only. The set of asymmetric measures from economic dependence or sanctions, to diplomatic, political, and informational measures are used to prevent an emergence of a conflict that would threaten Russia’s sovereignty and domestic stability. The purpose of this paper is to explore the Soviet roots of Active Measures and how the Soviet heritage is present at both the theoretical level and in concrete practices. Finally, insights from the conceptual analysis are applied in assessing the vulnerability of the Nordic countries, in particular Finland and Sweden, to Russian influence operations.